Perceptions of Male Students in Learning the Art of Dance at SMA Pembangunan Laboratorium UNP - Rizka Janarsi; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
The purpose of this study was to determine the perception of male students about dance learning at UNP Laboratory Development High School. This type of research is qualitative research using descriptive methods. The researcher himself is an instrument that carries out the process of planning, implementing, collecting data and communicating research results. Data were collected through observation, interviews, literature studies and documentation. Data analysis is carried out starting from data collection, data reduction, then data presentation then finalization and verification. The results proved that the understanding of male students of UNP Laboratory Development High School about dance learning is quite low, there are weaknesses that need to be improved, namely student interest in learning dance, teachers must pay more attention to the methods used and provide understanding to students, especially male students that male students can dance.